Analyzing Professional Competences of Future Teachers - Bakhmat, Liudmyla; Fursa, Iryna (My University, 2017)
The article deals with defining professional competences for future teachers training. Along with tracing back the origins and various interpretations of the concept, competences of science and English teachers are analyzed.
Bakhmat L. Analyzing Professional Competences of Future Teachers / L. Bakhmat, I. Fursa // Educational Researcher : American Educational Research Association. – 2017. – № 9 (2). – Vol. 46. – P. 693–698
Keywords: competence, competency, professional competences, components of professional competences, science teachers, English teachers